Supervision of Road and Bridge Maintenance by the Department of Water Resources, Highways, and Construction Development of Deli Serdang Regency - Zahra, Khairani; Trimurni, Februati (The Eastasouth Journal of Social Science and Humanities, 2025)
The Water Resources, Highways, and Construction Agency, established in 2022 in Deli Serdang Regency, oversees road and bridge maintenance, succeeding the Public Works and Spatial Planning Agency. This study evaluates the highways sector’s performance and public satisfaction using a descriptive qualitative approach. Data were collected through interviews, observations, documentation, and literature reviews, analyzed via method and data triangulation. Findings reveal that supervision involves setting standards, measurements, comparisons, and corrective actions. Standards focus on highway construction performance for road and bridge maintenance. Measurement includes investigation surveys, result reports, rehabilitation activities, progress reports, work calculations, and ratification. Comparisons assess performance against designs, with corrective actions addressing discrepancies. Despite challenges, the road and bridge maintenance sub-coordination staff performed effectively, covering all sections in Deli Serdang Regency, demonstrating optimal service delivery.